2015
DOI: 10.2967/jnmt.115.154997
|View full text |Cite
|
Sign up to set email alerts
|

Precise Localization of a Bile Leak with Hepatobiliary Scintigraphy

Abstract: Hepatobiliary scintigraphy (HBS) is a widely used modality to diagnose biliary injury. In patients with a history of trauma or surgery, the common presentations of bile leaks on HBS are a progressive collection of radiotracer outside the biliary system. However, the precise localization of a bile leak is usually not conveyed by noninvasive techniques including CT or ultrasound or even HBS. This case study of a patient with liver trauma demonstrates a direct bile leak sign leading to recognition of an exact bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…3 ). 50 The magnitude of the leak may also be assessed based on the quantity of tracer that has exited the biliary system into the perihepatic space. While useful in confirming a leak, cholescintigraphy is limited in its spatial resolution, making it challenging to identify the precise location of the leak.…”
Section: Diagnosismentioning
confidence: 99%
“…3 ). 50 The magnitude of the leak may also be assessed based on the quantity of tracer that has exited the biliary system into the perihepatic space. While useful in confirming a leak, cholescintigraphy is limited in its spatial resolution, making it challenging to identify the precise location of the leak.…”
Section: Diagnosismentioning
confidence: 99%
“…He had central hepatic laceration with extension into gallbladder fossa and peritoneal fluid, who underwent Hepato-biliary scintigraphy (HBS). 9 The report concluded that although the precise site of a bile leak is often difficult to detect with noninvasive techniques, it is possible with HBS.…”
Section: Bile Leaksmentioning
confidence: 99%